The Use of Nutmeg Shell as a Lightweight Concrete Material - Budiman, Budiman; Imran, Imran; WTP, James (INTEK: Jurnal Penelitian, 2020)
Lightweight concrete is concrete that has a lighter density than concrete in general. Nutmeg shell utilization as coarse aggregate is expected to be the added material in the lightweight concrete mixture. The purpose of this study is to determine characteristics of the concrete aggregate and the compressive strength of the concrete design based on the DOE (Department of Environment) method and the SNI Standard. In this research, the use of nugmet shell was varied as follows: 10%, 20%, 30%, 40% and 50% of the concrete weight. The research result shows that the amount of nugmet shell used into the concrete mixture affects the compressive strength of the concrete characteristics (fck’). The compressive strength of the concrete characteristics increases with the increase in the amount of nutmeg shell used in the concrete mixture. The compressie strength increases consecutively from  28.42 kg /cm2, 31.65 kg / cm2 to 32.68 kg /cm2 with the increase in the amount of nutmeg shell: 10%, 20% and 30%. Then, it decreases into 29 , 09 kg /cm2 and 27.38 cm2 with further increasing 40% and 50% nutmeg shell of the concrete weight. The average weight of the concrete mixture using nutmeg shell was 1202 kg/m3with the maximum compressive strength value of 3.2 MPa, thus it could be categorized as the lightweight concrete.